2016
DOI: 10.1186/s12967-015-0750-3
|View full text |Cite|
|
Sign up to set email alerts
|

NGF eye-drops topical administration in patients with retinitis pigmentosa, a pilot study

Abstract: Background Preclinical trials have shown beneficial effects of nerve growth factor (NGF) administration on visual function in animal models of retinitis pigmentosa (RP). The aim of this pilot study was to explore the potential efficacy of short term NGF eye drops treatment in patients affected by RP.Methods The trial consisted in 10 days daily administration of murine NGF as eye-drops for a total dose of 1 mg NGF/pt. Eight RP patients at an advanced stage of the disease were included in the trial. To monitor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The pathological process of RP is influenced by a spectrum of molecular, cellular, and tissue-level factors (Lemos Reis et al, 2015). In view of the enormous heterogeneity implied in etiology, RP patients always have highly variable onset points, progressive dynamics, and prognosis outcomes (Cai et al, 2014;Falsini et al, 2016). These variations make the accurate diagnosis extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological process of RP is influenced by a spectrum of molecular, cellular, and tissue-level factors (Lemos Reis et al, 2015). In view of the enormous heterogeneity implied in etiology, RP patients always have highly variable onset points, progressive dynamics, and prognosis outcomes (Cai et al, 2014;Falsini et al, 2016). These variations make the accurate diagnosis extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these patients demonstrated an increase in visual acuity, a temporary enlargement of the VF and an improvement in macular focal ERG findings. This study suggested that the application of NGF eye-drop is safe and efficient in at least some of the RP patients [25].…”
Section: Discussionmentioning
confidence: 65%
“…Topical administration of NGF therefore has been attempted and demonstrated to be effective experimentally 25,26,40,42 . Topical NGF is already approved for treatment in humans with neurotrophic keratitis 44 , and is safe, well tolerated and effective in patients 26,[44][45][46][47] . It has not been used for any other clinical ocular indication.…”
Section: Resultsmentioning
confidence: 99%